Associations of Cannabis Use across Adolescence and Early Adulthood With Health and Psychosocial Adjustment in Early Adulthood and Midadulthood in Men - Deborah M Capaldi; Stacey S Tiberio; David CR Kerr; Lee D Owen (SAGE Publishing, 2022)
Background: Associations between men's prior cannabis use and their physical and psychosocial adjustment were examined using prospective data across adolescence (ages 13-20 years), early adulthood (ages 20-30 years), and midadulthood (ages 30-38 years). The theoretical framework was based in developmental-contextual and lifespan approaches. Method: Models were tested using men in the Oregon Youth Study who had been studied since ages 9 to 10 years and who, in childhood, lived in neighborhoods with higher than average rates of delinquency. Cannabis use in adolescence was used to predict early adult outcomes (and early adult use to midadult outcomes). In addition, a set of covariates was added to the models, including childhood risk factors assessed at age 9 years (ie, family socioeconomic status; externalizing behaviors; and if available, the childhood proxy for the outcome [eg, age 9 intelligence scale]) and alcohol use in adolescence (or early adulthood). physical health outcomes included accidental injuries, problems resulting from a prior injury, body mass index, self-report health, and also pain and cardiovascular risk (blood pressure and pulse rate) in midadulthood. Psychosocial outcomes included income, housing insecurity, intelligence, depressive symptoms, psychosis symptoms, hostility/aggression, social problems, and attention problems. Results: Whereas there was almost no prediction from prior cannabis use to the physical health outcomes, there were comprehensive associations of cannabis use from the prior developmental period and psychosocial outcomes in both early adulthood and midadulthood. Conclusion: Cannabis use in prior developmental periods was associated with a broad range of types of poor psychosocial adjustment in adulthood.